Mangrove sediment quality index in Matang Mangrove Forest Reserve, Perak, Malaysia - Mohamad Pazi, Ahmad Mustapha (2020)
Mangrove forests have an integral role in the protection of ecosystem, hydrological and sedimentation regulatory functions. In addition, mangrove sediment can trap pollutants discharged through domestic, industrial and agricultural activities. Therefore, it is essential to assess sediment quality in the presence/absence of heavy metals that are toxic to most living organisms. Hence this study aims to develop a mangrove sediment quality index (MSQi) in Matang Mangrove Forest Reserve, Perak Peninsular Malaysia. The specific objectives of this study are: (i) to develop Mangrove Sediment Quality Index at Matang Mangrove Forest Reserve, (ii) to compare selected MSQi parameters between mangrove environment factors and (iii) to validate Mangrove Sediment Quality Index at Setiu Wetland, Terengganu and Kukup Island, Johor. The sampling areas were selected that relied on distinct levels of mangrove disturbance (highly disturbed, moderately disturbed and least disturbed). At 1.5 meter depth, sediments were sampled into five segments (0-15, 15-30, 30-50, 50-100 and 100-150 cm). A Total of 19 variables (Sand, Silt, Clay, EC, pH Water, N, P, K, Ca, Mg, Mn, Fe, Pb, Zn, Cu, Cd, Cr, Ni and Na) were analysed to determined sediment physico-chemical properties using the standard method of soil analysis. In developing MSQi, Principal Component Analysis (PCA) was used to find 4 important parameters then the MSQi modelling was developed using Microsoft excel to classify the level of mangrove sediment as I=Very Bad, II=Bad, III=Moderate, IV=Good and V=Excellent. According to the results of this study, the nutrient and heavy metal content came out to be within permissible range. Four parameters (Pb, Zn, Cr and Ni) were chosen by PCA to be included in MSQi. The MSQi result showed that Tiram Laut River, during the dry season, was moderately polluted under class III. During the wet season, MSQi of Tiram Laut River was less polluted under class IV. Tinggi River, during dry season, was under class III and moderately polluted, except at seaward at sediment depth of 30-50 and 50-100 cm it was under class IV with low pollution. On the other hand, during the wet season, Tinggi River was moderately to low polluted. Lastly, Sepetang River during dry season was found under class III with moderate pollution and with low pollution during the wet season. In term of MSQI validation results showed Ular River and Setiu River at Wetland Setiu Terengganu shows that season plays an important role in balancing the sediment pollutions. During dry season most of the areas are polluted, whereas during wet season the area becomes less. In case of mangrove zones and sediment depths, different results have been obtained for MSQi. Landward zone was more polluted than other zones except at Kukup Island where, seaward zone had more pollution during dry season and then changed to slightly polluted. Sediment depths can also influence pollution levels, which was observed in this study. As a conclusion of this study, MSQi development can be a benchmark and guideline in assessing sediment pollution in the mangrove ecosystem of Malaysia.